THE ESTIMATION OF THE RISK OF DEGRADATION OF THE SOILS OF ARARAT HOLLOW ON THE MODEL OF ARARAT REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The government has lost the main functions of management and the control of soil resources as a result of privatization of soils since 1990 which led to negative changes and aggravation of geoecological problems. In 1999 493.5 (0.4%) hectares of agricultural grounds were already out of use in the region. The classification of the degree of the origin of risk has been carried out according to the data of studies of the types of degradation soils of high-altitude zones. Three gradations of the degree of the risk of extraordinary ecological situation have been distinguished and mapped. The main problems for each area have been determined, the further aggravation of which may lead to the origin of extraordinary ecological situation of local level in the given area as a result of strengthening of anthropogenic load. The high degree of the risk of the origin of extraordinary ecological situation is characterized by considerable and weakly compensating changes and the loss of soils (salinization, bogging up), the average degree is characterized by partial losses of natural resources potential (spreading of soil erosion) and the low degree is characterized as the most weakly degrading with partial losses of soil (sand-pits and dumps of surface output of limestone).
Keywords: Ararat Hollow; Ararat Region; degradation soils